A revision of the hitherto neglected genus Topiris Walker, 1863 (Lepidoptera, Xyloryctidae) with taxonomic notes on the genus Athrypsiastis Meyrick, 1910 - Mark J. Sterling; Ben W. Price; David C. Lees (ZooKeys)
The genus Topiris Walker, 1863 is revised. This genus, previously neglected or deemed unrecognisable, comprised only Walker’s damaged and misrepaired type specimen of Topiris candidella Walker, 1863. Evidence is provided that this specimen was collected by Alfred Russel Wallace in 1855–56 in Sarawak, Malaysian Borneo. The mitogenome of this specimen was assembled using low coverage whole genome sequencing (genome skimming). The COI-5P portion of this mitogenome (658 bp) differs by 1–3 bp from two haplotypes sequenced from early 1990’s Brunei specimens. Another specimen recently discovered at NHMUK with an identical label to that of the type perfectly matches the Brunei specimens in its genitalia. Based on these four specimens, we present a fuller description of the morphology of T. candidella. Topiris includes the following additional species authored by Sterling and Lees: Topiris albidella sp. nov., T. albogrisella sp. nov., T. cinderella sp. nov., T. digiticosta sp. nov., T. lacteella sp. nov., T. madonna sp. nov., T. meyricki sp. nov., T. ochrotincta sp. nov., T. schneeweissella sp. nov., T. sericella sp. nov., and T. thunbergella sp. nov. The following new combinations are also established: T. salva (Meyrick, 1932), comb. nov. and T. sampitella (Lvovsky, 2014), comb. nov. The type of Athrypsiastis salva Meyrick is confirmed as lost and so a neotype and paraneotype of this species are designated. A published mitogenome of “Linoclostis gonatias” is shown to be correctly identified as T. salva, and references to L. gonatias, identified in some literature as a pest of Theaceae, are likely misidentified. The genus Topiris is divided into three groups, the candidella group, the salva group, and the albidella group, based on characters in the male genitalia. The candidella group and albidella group are supported sub-clades of Topiris. The phylogenetic placement of Topiris and Athrypsiastis within ‘core’ Xyloryctidae (as subtended by its type species, X. luteotactella) is confirmed by analysis of COI and seven nuclear genes, whereas the genera Eumenodora Meyrick, 1906 and Izatha Walker, 1864 do not fall within this clade. The morphology of Athrypsiastis phaeoleuca Meyrick, 1910 (the type species of Athrypsiastis; Xyloryctidae) is more fully described. The following new species authored by Sterling and Lees are described: Athrypsiastis cheesmanae sp. nov., A. edelweissella sp. nov., and A. penumbrella sp. nov. Two taxa are newly combined: Athrypsiastis halmaherella (Lvovsky, 2014), comb. nov. and Paralecta rosiflora (Meyrick, 1930), comb. nov.